Imagens surrealistas nas obras Poesia completa de Pio Vargas e Congresso espiritual dos ranúnculos de Fabrício Clemente - Monteiro, Amanda Cristinny Santos (2023)
This research project proposes a study on the Surrealist European Vanguard in Brazilian poetry from the point of view of authorship studies, observing how and why certain poets followed Surrealism in poetry. Therefore, it will be taken into account to analyze two poetic works of contemporary writers from Goiás, the Complete Poetry of Pio Vargas, published in 2014 and the book Congresso Espiritual dos Ranúculos of 2013, in the perspective of selecting poems in which the influence of Surrealism is evidenced as a contribution in the production of poets from Goiás. It is widely publicized in all historical studies of the literature produced in Goiás that Modernism arrives in the State with delay and timidly, but it is necessary to take into account that this literary movement had as one of the precepts the non-imposition, therefore, it was not mandatory . However, little is investigated about how this adherence occurs and which tendencies of the modernist Vanguard represent the lines of force of Goiás poetry from the end of the last century to the present day. Thus, the intention of the research is to show that, although there are not many poets considered surrealist in Brazilian literature, those mentioned above adopted the surrealist way of representing reality, guaranteeing a prominent place in national poetry. The study aims, with the support of theories about the constitution of images, to discuss a form of representation that relates elements of the subject's reality with a dream, which is one of the possibilities of representing the real in lyric poetry.